OPTIMASI PENJADWALAN PERAWAT DI RUANG UGD RSUD LAPANGAN SAWANG MENGGUNAKAN METODE NON-PREEMPTIVE GOAL PROGRAMMING - Lowryk O. Lahunduitan; James U.L Mangobi; Vivian E. Regar (Discovery : Jurnal Ilmu Pengetahuan, 2022)
The emergency room which requires a full 24-hour nurse certainly needs to pay attention to the right schedule. To get an optimal schedule, it is necessary to divide nurses according to the needs of the right shift. Schedules that are made manually often violate or pay less attention to the applicable rules. Based on the existing rules in the hospital, constraints are divided into main constraints and additional constraints which are modeled and solved using the Non-Preemptive Goal Programming method with the objective function being to minimize the advantages or disadvantages of additional constraints. Furthermore, for the computational process assisted by the LINGO 19.0 application. From the results and discussion, it is found that the optimal schedule using the Non-Preemptive Goal Programming model is fulfilled for every existing constraint. Keywords: Schedule, Nurse, Goal Programming, Non-Preemptive Goal Programming